2017
DOI: 10.1186/s13049-017-0460-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect on the patient flow in local health care services after closing a suburban primary care emergency department: a controlled longitudinal follow-up study

Abstract: BackgroundIt has not been studied what happens to patient flow to EDs and other parts of local health care system if distances to ED services are manipulated as a part of health policy in urban areas.MethodsThe present work was an observational and quasi-experimental study with a control and it was based on before-after comparisons. The impact of terminating a geographically distant suburban primary care ED on patient flow to doctors in local public primary care EDs, office-hour primary care, secondary care ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…The studies used a variety of observational designs, with before-after and cohort designs being most common. Knowles et al 2 and Mustonen et al 11 were the only studies with independent control sites where no reconfiguration had taken place.…”
Section: Reconfiguration Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies used a variety of observational designs, with before-after and cohort designs being most common. Knowles et al 2 and Mustonen et al 11 were the only studies with independent control sites where no reconfiguration had taken place.…”
Section: Reconfiguration Studiesmentioning
confidence: 99%
“…In the reconfiguration group, the most common design was before-after and only four studies compared outcomes between settings with and without changes in distance/time. 2,5,9,11 Association studies generally used a cohort or cross-sectional design (see Table 2).…”
Section: Risk-of-bias Assessmentmentioning
confidence: 99%
“…This suggests the possibility that the effect of increased distance or time may be diluted in the general UEC population by the presence of patients with less serious conditions and minimal short-term risk of death. However, one of the largest studies found no change in in-patient mortality for either the population as a whole or subgroups with specific emergency conditions [12]. The implications for the health system as a whole of reconfiguring a key part of UEC might be conjectured as being substantial.…”
Section: Main Findingsmentioning
confidence: 98%
“…The studies used a variety of observational designs, with before-after and cohort designs being most common. Knowles et al [3] and Mustonen et al [12] were the only studies that compared reconfiguration sites with independent control sites where no reconfiguration had taken place.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation